On the Use of Optically Stimulated Luminescent Dosimeter for Surface Dose Measurement during Radiotherapy - Yusof, F.H.; Ung, N.M.; Wong, J.H.D.; Jong, W.L.; Ath, V.; Phua, V.C.E.; Heng, S.P.; Ng, K.H. (Public Library of Science, 2015)
This study was carried out to investigate the suitability of using the optically stimulated luminescence dosimeter (OSLD) in measuring surface dose during radiotherapy. The water equivalent depth (WED) of the OSLD was first determined by comparing the surface dose measured using the OSLD with the percentage depth dose at the buildup region measured using a Markus ionization chamber. Surface doses were measured on a solid water phantom using the OSLD and compared against the Markus ionization chamber and Gafchromic EBT3 film measurements. The effect of incident beam angles on surface dose was also studied. The OSLD was subsequently used to measure surface dose during tangential breast radiotherapy treatments in a phantom study and in the clinical measurement of 10 patients. Surface dose to the treated breast or chest wall, and on the contralateral breast were measured. The WED of the OSLD was found to be at 0.4 mm. For surface dose measurement on a solid water phantom, the Markus ionization chamber measured 15.95% for 6 MV photon beam and 12.64% for 10 MV photon beam followed by EBT3 film (23.79% and 17.14%) and OSLD (37.77% and 25.38%). Surface dose increased with the increase of the incident beam angle. For phantom and patient breast surface dose measurement, the response of the OSLD was higher than EBT3 film. The in-vivo measurements were also compared with the treatment planning system predicted dose. The OSLD measured higher dose values compared to dose at the surface (Hp(0.0)) by a factor of 2.37 for 6 MV and 2.01 for 10 MV photon beams, respectively. The measurement of absorbed dose at the skin depth of 0.4 mm by the OSLD can still be a useful tool to assess radiation effects on the skin dermis layer. This knowledge can be used to prevent and manage potential acute skin reaction and late skin toxicity from radiotherapy treatments.